2013
DOI: 10.12968/ijpn.2013.19.1.16
|View full text |Cite
|
Sign up to set email alerts
|

External mirroring of inner chaos: blogging as experienced by the relatives of people with cancer

Abstract: Blogging was seen as a complement to professional care that contributed to the prevention of ill health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Other descriptive studies (n = 12; 17.4%; Table 2) used surveys, 11,23,24,28,40,43,46,59,60,63,65,74 in-depth interviews, 47 focus groups, 48 social network analyses, 20,68 a mix of measurement techniques, 8,9,13,22,30,39 Web metrics, 72,73 and frequencies 62 to describe how users employed social media to obtain and receive cancer information. It is important to note that only 1 of these studies reviewed the accuracy of information posted on a social media site (YouTube); it reported that roughly 75% of all videos had either fair or poor information about prostate cancer screening.…”
Section: Resultsmentioning
confidence: 99%
“…Other descriptive studies (n = 12; 17.4%; Table 2) used surveys, 11,23,24,28,40,43,46,59,60,63,65,74 in-depth interviews, 47 focus groups, 48 social network analyses, 20,68 a mix of measurement techniques, 8,9,13,22,30,39 Web metrics, 72,73 and frequencies 62 to describe how users employed social media to obtain and receive cancer information. It is important to note that only 1 of these studies reviewed the accuracy of information posted on a social media site (YouTube); it reported that roughly 75% of all videos had either fair or poor information about prostate cancer screening.…”
Section: Resultsmentioning
confidence: 99%
“…They are useful to find people with similar experiences, and help them in their grief process and to preserve memories. Contrarily, blogs can also be perceived by readers as tasteless “reality shows” [ 24 ].…”
Section: Reviewmentioning
confidence: 99%
“…She claims that care is founded in us within the office of being human and thus natural in all of us, then our ability to use that develops depending on social and cultural conditions. Andersson ( 2013 ) claims that natural care is part of what makes us human. Rafii et al ( 2007 ) state that natural care occurs spontaneously and without thinking, in contrast to professional care that is reflected on in relation to ethics and evidence.…”
Section: Introductionmentioning
confidence: 99%